Handbook of Image-Guided Brachytherapy - Mayadev, Jyoti; Benedict, Stanley H.; Kamrava, Mitchell (Springer International Publishing : Imprint: Springer, 2017)
This handbook provides a clinically relevant, succinct, and comprehensive overview of image-guided brachytherapy. Throughout the last decade, the utility of image guidance in brachytherapy has increased to enhance procedural development, treatment planning, and radiation delivery in an effort to optimize safety and clinical outcomes. Organized into two parts, the book discusses physics and radiobiology principles of brachytherapy as well as clinical applications of image-guided brachytherapy for various disease sites (central nervous system, eye, head and neck, breast, lung, gastrointestinal, genitourinary, gynecologic, sarcoma, and skin). It also describes the incorporation of imaging techniques such as CT, MRI, and ultrasound into brachytherapy procedures and planning. Featuring procedural and anesthesia care, extensive images, contouring examples, treatment planning techniques, and dosimetry for the comprehensive treatment for each disease site, Handbook of Image-Guided Brachytherapy is a valuable resource for practicing radiation oncologists, physicists, dosimetrists, residents, and medical students. .
Keywords: Medicine.; Gynecology.; Radiotherapy.; Oncology.; Urology.; elektronické knihy; electronic books